Implantation of Bacillus pseudomycoides Chromate Transporter Increases Chromate Tolerance in Bacillus subtilis - Chromiková, Zuzana; Chovanová, Romana Kalianková; Tamindžija, Dragana; Bártová, Barbora; Radnović, Dragan; Bernier-Latmani, Rizlan; Barák, Imrich (Frontiers in Microbiology, 2022)
Chromium of anthropogenic origin contaminates the environment worldwide. The toxicity of chromium, a group I human carcinogen, is greatest when it is in a hexavalent oxidation state, Cr(VI). Cr(VI) is actively transported into the cell, triggering oxidative damage intracellularly. Due to the abundance of unspecific intracellular reductants, any microbial species is capable of bio-transformation of toxic Cr(VI) to innocuous Cr(III), however this process is often lethal. Only some bacterial species are capable of sustaining the vegetative growth in the presence of a high concentration of Cr(VI) and thus operate as self-sustainable bioremediation agents. One of the successful microbial Cr(VI) detoxification strategies is the activation of chromate efflux pumps. This work describes transplantation of the chromate efflux pump from the potentially pathogenic but highly Cr resistant Bacillus pseudomycoides environmental strain into non-pathogenic but only transiently Cr tolerant Bacillus subtilis strain. In our study, we compared the two Bacillus spp. strains harbouring evolutionarily diverged chromate efflux proteins. We have found that individual cells of the Cr-resistant B. pseudomycoides environmental strain accumulate less Cr than the cells of B. subtilis strain. Further, we found that survival of the B. subtilis strain during the Cr stress can be increased by the introduction of the chromate transporter from the Cr resistant environmental strain into its genome. Additionally, the expression of B. pseudomycoides chromate transporter ChrA in B. subtilis seems to be activated by the presence of chromate, hinting at versatility of Cr-efflux proteins. This study outlines the future direction for increasing the Cr-tolerance of non-pathogenic species and safe bioremediation using soil bacteria.